Toxicological response of silver catfish (Rhamdia quelen) after acute exposure to a commercial insecticide containing thiamethoxam. Issue 8 (2nd August 2020) - Salbego, Joseânia; Seben, Débora; Sippert, Leticia Raquel; Gressler, Luciane Tourem; Arruda da Cunha, Jessyka; Zanella, Renato; de Almeida Vaucher, Rodrigo; Marchesan, Enio; Baldisserotto, Bernardo; Loro, Vania Lucia; Golombieski, Jaqueline Ineu
Abstract: This study assessed the hematological, enzymatic and osmoregulatory responses of silver catfish ( Rhamdia quelen ) exposed to sublethal concentrations (1.125 and 3.750 µg/L) of a commercial thiamethoxam-containing insecticide used on rice crops. Groups of 6 fish per tank (in triplicate, n = 3, total 54 fish) were exposed for up to 96 h to different concentrations of the compound. After this period, fish were placed in clean water for 48 h. Two fish from each tank (6 per treatment) that had been exposed to the insecticide for 24 h were anesthetized with eugenol and blood was collected to evaluate hematological and biochemical parameters. Blood, liver and muscle were collected for determination of metabolic parameters, plasma cortisol, Cl -, Na + and K + levels and H + -ATPase and Na + /K + -ATPase activity in the gill. H + -ATPase activity was higher in fish exposed to 1.125 µg/L insecticide at 24 h compared to control (0.0 µg/L). Differences in cortisol levels were evidenced throughout the experimental period. These results indicated that exposure to the insecticide changed the hematological, biochemical and metabolic profile of the animals, suggesting concern about environmental safety. Therefore, we discourage the use of this pesticide in areas that come into contact with water bodies inhabited by fish.